2022
DOI: 10.1002/ps.7038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of herbicide specificity of CYP81A cytochrome P450s from rice and a multiple‐herbicide resistant weed, Echinochloa phyllopogon

Abstract: BACKGROUND: CYP81A cytochrome P450s (CYP81As) play a key role in herbicide detoxification in Poaceae plants. Crop CYP81As confer natural tolerance to multiple herbicides, whereas CYP81As in weeds disrupt herbicide action. Identifying differences in CYP81A herbicide specificity between crops and weeds could provide valuable information for controlling weeds. In this study, we quantitatively compared herbicide specificity between CYP81A6 from rice (Oryza sativa) and CYP81A12 and CYP81A21 from a weed, Echinochloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Cross resistance may be caused by a single enzyme or by the combination of multiple ones participating in any of the three phases of herbicide metabolism. For example, single CYP450s and GSTs have been shown to metabolize herbicides from multiple SoA groups 12–17 . Additionally, multiple genes encoding different enzymes can be co‐expressed (and potentially co‐regulated), where each enzyme could play a role in the detoxification process of multiple herbicides.…”
Section: Mechanisms Of Herbicide Cross Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Cross resistance may be caused by a single enzyme or by the combination of multiple ones participating in any of the three phases of herbicide metabolism. For example, single CYP450s and GSTs have been shown to metabolize herbicides from multiple SoA groups 12–17 . Additionally, multiple genes encoding different enzymes can be co‐expressed (and potentially co‐regulated), where each enzyme could play a role in the detoxification process of multiple herbicides.…”
Section: Mechanisms Of Herbicide Cross Resistancementioning
confidence: 99%
“…A few recent studies in weed science have utilized protein structure prediction with docking simulations. For instance, Ha et al 12 applied a docking analysis for herbicide affinity identification using the identified CYP81A in Echinochloa phyllopogon and its rice homologs. GSTs and UGTs also should be analyzed for their affinity with herbicide molecules.…”
Section: Approaches For Identification Of Regulatory Elements and Cro...mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Numerous Phase II metabolites of DU in crops are still unknown and need to be discovered and studied. More importantly, several key herbicide-detoxifying genes encoding metabolizing enzymes have been identified recently, such as CYP81A, CYP709C, ARGT1, and GSTF1, 9,14,15 whereas a substantial knowledge gap still exists in the detoxifying genes responding to DU stress and their genetic regulatory mechanism pertaining to the generation and distribution of DU derivatives in crops. The characterization of herbicidedetoxifying genes and the elucidation of their molecular signal pathway are great advances in understanding the NTSR and supplying useful information for developing crop protection schemes.…”
Section: ■ Introductionmentioning
confidence: 99%